Teratomas of the ovaries in girls from the position of a surgeon - N A Buralkina; V D Chuprynin; Yu S Golitsina; E V Uvarova; A Yu Zhurba; A A Kuzemin; A V Asaturova; N V Zaitsev; V V Kometova; S S Lunkov (IP Berlin A.V., 2017)
Among ovarian tumors, germinogenic tumors occur in 25.9% of cases, develop from the polypotent highly specialized germinogenic epithelium of the gonads. Most germinogenic tumors are mature (benign) cystic teratomas (95%), malignant germinogenic tumors occur in only 3-5% of cases. The only reasonable method of treating these tumors is surgery, which is associated with losses of the ovarian reserve. The article presents the clinical and anamnestic characteristics of girls aged 7 to 17 years with ovarian teratomas, describes the structure of the surgical interventions (access, volume of operations) with the analysis of the histological conclusion of the remote formations.